Tokenism or actual participation of primary school children: Children’s views on their democratic participation at school - Björnsdóttir, Elín Helga; Rúnarsdóttir, Eyrún María; Kristinsdóttir, Guðrún (Menntavísindasvið Háskóla Íslands, 2023)
The United Nations Convention on the Rights of the Child (UNCRC) is an international human rights agreement concerning children. It embodies the idea that every child should be recognised, respected, and protected as a rights holder and a unique and valuable human being. All rights are important and cannot be taken away.According to article twelve in the UNCRC, children have the right to give their opinions freely on issues that affect them, and adults should listen and take children seriously. Scholars believe that article twelve is the most tenuous children’s right. Research shows that most children do not know their rights and do not necessarily voice them as adults do. Despite that, decisions relating to children’s matters are often made without consulting with them.Increasing emphasis is placed on the rights and participation of children. Still, to ensure their rights under the convention, it is important that everyone, children, and adults, know about it. By 2030, all local authorities in Iceland should have started the implementation of the UNCRC. One way is to use UNICEF’s concept of Rights Respecting School. A Right Respecting School is a community where children’s rights are learned, taught, practised, respected, protected, and promoted. According to research, the implementation of the UNCRC does have a positive effect on all aspects of school life; children become more engaged in school decision-making. In addition, research shows that children have more positive attitudes toward diversity in society.This study aims to shed light on children’s experience and knowledge of democratic participation and to research the benefits of education about UNCRC in schools. Participants in the study were 43 students in 4th and 8th grade, attending four primary schools in Akureyri and Eyjafjarðarsveit, who participated in focus group interviews consisting of 5–6 in each group. Thematic analysis was used to analyse the data by reading, rereading, and systematically coding interviews. This analysis revealed two ...